2022
DOI: 10.3390/healthcare10112324
|View full text |Cite
|
Sign up to set email alerts
|

Association between Sleep Duration and Symptoms of Depression Aged between 18 and 49: The Korea National Health and Nutrition Examination Survey (KNHANES Ⅶ) from 2016 to 2018

Abstract: This study aimed to determine the association between symptoms of depression and sleep duration in a representative sample of the Korean population. Using national cross-sectional data from the seventh Korea National Health and Nutrition Examination Surveys (KNHANES-VII), 5461 adults aged 18–49 years were analyzed using logistic regression models. The proportions of participants with total daily sleep durations (24 h) of <6 h, 6–8 h, and ≥9 h were 26.2%, 60.6%, and 13.3%, respectively. The proportions of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Furthermore, it is posited by scholars that sleep restriction activates the hypothalamic-pituitary-adrenal axis, thereby exacerbating depressive symptoms ( 45 ). Additionally, inadequate sleep reduces productivity, which in turn increases the likelihood of aggressive behavior and may ultimately contribute to depression and suicidal issues ( 46 ). Alternatively, it has been hypothesized that individuals with shorter sleep durations may have more time for reflective thoughts, leading to adverse outcomes associated with depression ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is posited by scholars that sleep restriction activates the hypothalamic-pituitary-adrenal axis, thereby exacerbating depressive symptoms ( 45 ). Additionally, inadequate sleep reduces productivity, which in turn increases the likelihood of aggressive behavior and may ultimately contribute to depression and suicidal issues ( 46 ). Alternatively, it has been hypothesized that individuals with shorter sleep durations may have more time for reflective thoughts, leading to adverse outcomes associated with depression ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous research findings using these data have been published, and research on depression is currently being undertaken. Using the KNHANES V-VII (2010-2018) data, it has been reported that depression is associated with low intake of fruits and vegetables [82], low consumption of curry rice [83], seaweed and mushroom [84], sugar-sweetened beverages consumption (≥ 1/day) [85], short sleep (≤ 6 h) [86], increased work-related physical activity, decreased recreational physical activity [84,87], poor dietary habits [88,89], gender difference, night eating, and nutritional adequacy [90] in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, depression was defined as present or not present based on prior physician diagnosis from participant survey responses. 32,33 Finally, age and sex 34 were included in the analyses as covariates due to their ability to possibly confound the relationship between HL, voice disorder, and depression. Age is particularly important to control for as age is a frequently reported risk factor for both HL 35 and voice disorders.…”
Section: Variablesmentioning
confidence: 99%